2015
DOI: 10.1007/s10792-015-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of uveitis at the Apex Institute for Eye Care in India: Results from a prospectively enrolled patient data base (2011–2013)

Abstract: The purpose of the study was to identify the clinical and etiological profile of uveitis at the apex institute for eye care in India. This is a prospective, prevalence study. 980 consecutive patients with uveitis referred to uvea clinic, Dr. RP Centre for Ophthalmic Sciences (Ophthalmology division, All India Institute of Medical Sciences). Demographic data of each patient were noted and a thorough ocular examination including slit lamp examination and dilated fundus evaluation was carried out. OCT and fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…131,153,188,248 The family of HHV includes HSV-1, HSV-2, VZV, Epstein-Barr virus (EBV), and CMV. HHV is an important infectious cause of ocular inflammation.…”
Section: Viral Posterior Uveitismentioning
confidence: 99%
See 3 more Smart Citations
“…131,153,188,248 The family of HHV includes HSV-1, HSV-2, VZV, Epstein-Barr virus (EBV), and CMV. HHV is an important infectious cause of ocular inflammation.…”
Section: Viral Posterior Uveitismentioning
confidence: 99%
“…55,131,150,153 Uveitis can occur at any age, but the mean age of incidence is between 30 to 40 years in most studies. 12,55,131,150,153,188,248 About 60%–80% of uveitis occurs between the ages of 20 to 50 years. 242 In terms of anatomic classification, anterior uveitis is the most common form of uveitis, followed by panuveitis, posterior uveitis, and intermediate uveitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found 5% of our patients having uveitis in association with past or current definitive diagnosis of pulmonary or extrapulmonary tuberculosis. [26] We are yet to consider a diagnosis of presumed ocular tuberculosis as a distinct entity and do not treat patients with antitubercular drugs due to several reasons. A few of these being lack of Level 1–Level 2 evidence, suggested clinical, serological (nucleic acid amplification assays and interferon gamma release assays [IGRAs]) and tissue (aqueous and vitreous) approaches having several limitations and unanswered questions, known side effects of antitubercular drugs (14.1%) and concerns of promoting development of drug-resistant strains.…”
Section: Clinical Studiesmentioning
confidence: 99%